2018
DOI: 10.1007/s10067-018-4049-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between IL-17A/F, IL-23, IL-35 and IL-12/-23 (p40) levels in peripheral blood lymphocyte cultures and disease activity in Behcet’s patients

Abstract: Behcet's disease is a chronic multisystemic disease with remissions and relapses. Several studies have shown that immune mechanisms play an important role in the development of the disease. In order to assess the association of disease activity with IL-17A/F, IL-23, IL-12/23 (p40) and IL-35 expression, we aimed to investigate production of these cytokines in peripheral blood mononuclear cells (PBMCs) from Behcet's patients and normal controls. Furthermore, we included Systemic Lupus Erythematosus (SLE) as dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
0
17
1
2
Order By: Relevance
“…Therefore, IL-23 plays an important role in the expansion and survival of Th17 cells. High levels of IL-23 have been reported in PBMCs from active BD patients (52, 58). These results suggest that the serum IL-17A/F levels parallel the IL-23 levels in patients with active BD, that the active inflammatory state may lead to the differentiation of Th17 cells, and that the IL-17/23 axis has a significant role in mediating inflammatory responses in BD.…”
Section: The Role Of Autoimmune T Cells and Cytokines In The Pathogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, IL-23 plays an important role in the expansion and survival of Th17 cells. High levels of IL-23 have been reported in PBMCs from active BD patients (52, 58). These results suggest that the serum IL-17A/F levels parallel the IL-23 levels in patients with active BD, that the active inflammatory state may lead to the differentiation of Th17 cells, and that the IL-17/23 axis has a significant role in mediating inflammatory responses in BD.…”
Section: The Role Of Autoimmune T Cells and Cytokines In The Pathogenmentioning
confidence: 99%
“…Sonmez et al reported that a low level of the Treg cytokine IL-35 was negatively correlated with the number of Th17 and Treg cells. The level of IL-35 in patients with inactive BD and healthy controls was higher than that in patients with active BD, a finding that could be explained by the plasticity between Th17 cells and Treg cells (58).…”
Section: The Role Of Autoimmune T Cells and Cytokines In The Pathogenmentioning
confidence: 99%
“…35 Decreased serum levels of IL-35 in patients with the active stage of Behcet disease compared to inactive Behcet patients and healthy controls might be a sign of the flexibility of T reg lymphocytes depending on the stage of the disease. 36…”
Section: Il-35 In Psychiatric and Neurological Conditionsmentioning
confidence: 99%
“…Foxp3 inhibits Th17 differentiation by antagonizing the RORγt function [62]. Sonmez et al [63] reported that IL-17A/F levels increased parallel to IL-23 levels in BD and IL-35 levels were lower in active BD patients than the inactive BD patients, which may be a plasticity between Th17 and Treg cells according to the state of disease activity.…”
Section: Plasticitymentioning
confidence: 99%
“…Liu et al reported that significantly higher levels of IL-17 are detected in active BD patients and stimulation with IFN-α decrease IL-17 production [17]. In vitro study showed that IFN-α does not directly regulate the Th1/Th17 balance in BD but rather promotes a regulatory Th1 response through IL-10 secretion [63]. IFN-α activity was mediated via STAT2 phosphorylation [17].…”
Section: Antibodies To Ifn-αmentioning
confidence: 99%